PENGEMBANGAN ALAT UKUR BATAS KAPASITAS TAS SEKOLAH ANAK BERBASIS MIKROKONTROLER - Novia Utamu Putri; Putri Oktarin; Risky Setiawan (Jurnal Ilmiah Mahasiswa Kendali dan Listrik, 2020)
Backpacks are often used by school children as a container or a place to carry their school materials and equipment, so these types of backpacks are very popular with school children. The large number of students wearing backpacks to school can be proven from the results of a survey conducted at SD N Bumisari, Natar District, South Lampung. Of the total number of subjects, 456 elementary school students carried 404 students (88.6%), and 52 students (11.4%) carried sling bags. But they rarely pay attention to the weight of the burden on the bag he carries everyday which turns out to cause injury to back pain.The tool is made in the form of a wearable device where the tool is in the form of a backpack that can be carried anywhere without having to require AC current as input voltage to the tool, because the power uses DC current with a voltage of 5V, the device is made using a microcontroller supported by a 10 kg loadcell sensor, modules HX711, keypad, plus an indicator component in the form of a buzzer. If the bag load exceeds the safe limit, the buzzer indicator will sound.